The Role of 18F-FDG PET/CT in Suspected Intraocular Sarcoidosis and Tuberculosis. (3rd April 2021) - Burger, C.; Holness, J. L.; Smit, D. P.; Griffith-Richards, S.; Koegelenberg, C. F. N.; Ellmann, A.
ABSTRACT: Purpose : To determine the utility of fluorine-18 fluorodeoxyglucose Positron Emission Tomography Computed Tomography (FDG PET/CT) in patients with suspected ocular sarcoidosis (OS) or intraocular tuberculosis (IOTB) in a resource-constrained, TB endemic area. Methods : Independent review of the FDG PET/CTs, Computed Tomography (CT) scans and chest radiographs (CXRs) of patients with suspected OS or IOTB and inconclusive conventional workup. Results : Twenty-nine PET/CTs and CXRs were reviewed, with 38% of PET/CTs and CTs demonstrating evidence of TB or sarcoidosis, compared to 21% of CXRs. The sensitivity, specificity, positive and negative predictive values for PET/CT and CT were similar - 85.7%, 95.5%, 85.7% and 95.5% for OS, and 33.3%, 100%, 100% and 68% for IOTB respectively and for CXR, 57.1%, 100%, 100% and 88% for OS, and 16.7%, 100%, 100% and 63% for IOTB. Conclusion : PET/CT added no significant additional benefit over Chest CT in patients with suspected OS or IOTB.